Pengaruh Jumlah Penduduk terhadap Pertumbuhan Ekonomi Provinsi Jambi Melalui Tingkat Pendidikan dan Tenaga Kerja sebagai Variabel Intervening - Rosita, Ratih; Asrini, Asrini; Veronica, Deka; Bansa, Yorina An’guna; Vina, Vina (Universitas Batanghari Jambi, 2025)
This study aims to determine and analyze the influence of population size on economic growth through education level and workforce in Jambi Province during the period 2010-2022. This study uses path analysis. The results of this study conclude that there is a direct influence between population size, education level, and workforce on economic growth in Jambi Province during the period 2010-2022. This study also found that the education level variable is able to moderate the influence of population size on economic growth, but the workforce variable is not able to moderate the influence of population size on economic growth in Jambi Province during the period 2010-2022.